Who pays for carbon dioxide removal? Public perceptions of risk and fairness of enhanced rock weathering in the UK - Kate O’Sullivan; Nick Pidgeon; Karen Henwood; Fiona Shirani; Harriet Smith (Humanities & Social Sciences Communications)
Abstract Carbon dioxide removal (CDR) is increasingly recognised as necessary to achieve net zero emissions. Enhanced rock weathering (ERW) is a novel CDR approach with large mitigation potential. With undefined social and environmental costs, and evolving economic and governance systems, ERW raises issues for public acceptance. A literature gap exists regarding how local communities view the possibility of at-scale deployment in their area. We address this with data from five UK public workshops to identify conditions under which communities potentially impacted by ERW consider deployment fair and acceptable. We show that public acceptance is conditional upon place-sensitive deployment pathways that reflect how place is valued. Analysis highlights opportunities to minimise risk and maximise benefits experienced locally; the importance of transparent governance and monitoring; and unbiased, balanced communication of impacts. Conversely, our research also reveals conditions that might make deployment unacceptable to local communities, including being ineffective as a CDR, environmental contamination connected to ecosystems, the absence of remediation plans, and mitigation deterrence through false carbon accounting. Understanding and incorporating public perceptions and preferences into emergent governance systems is essential if they are to be fair, effective and representative of societal concerns.